MODEL PENDIDIKAN BERWAWASAN KEBANGSAAN BAGI ANAK USIA DINI SEBAGAI SARANA INTEGRASI BANGSA - Purwastuti, L. Andriani (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->The aim of this research was to develop a model of civics education for early childhood as a means of national integration, based on the kindergarten curriculum and early childhood psychology. The curriculum has been designed by using local material especially coastal area potentials. The syudy was conducted by using the research and development approach/design. Data collection was done by a survey procedure in 14 kindergartens in Yogyakarta Province; namely 5 kindergartens from Kulonprogo District, 4 kindergartens from Bantul District, and 5 kindergartens from Gunungkidul District. Initial results indicated that the curriculum that is currently used in kindergarten is the Competency-based Curriculum (CBC). Several teachers reported a lack in the educative plays at school. Teachers reported their realization that the local potentials as natural resources at the coastal area have not been used optimallty. Civic education in in the curriculum was limited to integration in the “Tanah Air” theme. This study was able to develop a civic eduvation model with the integrative thema of Daily Scenario (SKH) for early childhood education. The study resulted in 3 books: 1) Integrative-Thematic Learning Design, 2) Integrative Thematic Learning Guidance, and 3) Resources Plays for Thematic Integrative Learning by Using Natural Resources and Local Material. The books were reviewed and validated by experts in early childhood education and experts in teaching-learning media